A New Science for a Post-Frontier World - Worster, Donald (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2020)
The driving force behind the North American frontier were waves of economic migrants from Europe and their offspring, competing against the indigenous people and eventually replacing them. But those waves were backed up by the power of the American and Canadian nation states, with their well-armed military, their well funded railroads, and other technology and capital. Science too was initially on the side of the invaders. But after World War One that frontier began to run out of free, abundant land. Then began what I will call a “post-frontier” science, especially ecological in content, that represented a very different attitude toward the white man’s conquest. Scientists like Frederick Clements, John C. Weaver, Paul Sears, and Stan Rowe, all natives to the Great Plains, laid the foundations for what is now a powerful critique of frontier agriculture. This article aims to summarize that critique briefly but focus mainly on the more recent work of Wes Jackson, founder and longtime president of the Land Institute. He has strongly criticized the frontier ethos for its the lack of understanding of the native ecology of the grasslands. In its place he has offered a vision of “perennial polyculture,” using nature as a model for agriculture in an era of limits. That model has not only been making a growing impact on American thinking but has now spread to other continents. Will the end of this frontier cycle and scientific reappraisal turn out to be what Jackson calls a “new agriculture,” one based on learning from the past and one that can change farming all over the world?